SOSIALISASI DAN OPTIMALISASI E-LEARNING BAHASA INGGRIS DAN BIOLOGI MENGGUNAKAN EDMODO KEPADA MAHASISWA PRODI PETERNAKAN UNIMOR - Siahaan, Desta Gloria; Pardosi, Lukas (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
One of the e-learning platforms that can be utilized during the Covid-19 pandemic is Edmodo. Edmodo learning media which is very functional, besides being able to be used for students and lecturers, can also be used by parents. Assignments were given through the assignment and quiz features that have a time limit, so they can practice discipline in doing assignments. The objectives of implementing this activity are; First, providing the concept and socialization of the use of Edmodo for the learning process. Second, providing knowledge on how to use and apply the features contained in the Edmodo platform to facilitate the English learning process. The target of this service was Animal Husbandry II C students who in this semester are studying English and Biology. This community service was able to provide knowledge to use the Edmodo e-learning platform for free to support conventional learning during this covid-19 pandemic. This activity lasted for 1 day in one of the room of the Faperta Unimor building.